2021
DOI: 10.3389/fnano.2021.644734
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Surface Coating of Iron Oxide Nanoparticles on Magnetic Resonance Imaging Relaxivity

Abstract: Iron oxide nanoparticles (IONPs) with acceptable biocompatibility and size-dependent magnetic properties can be used as efficient contrast agents in magnetic resonance imaging (MRI). Herein, we have investigated the impact of particle size and surface coating on the proton relaxivity of IONPs, as well as engineering of small IONPs' surface coating as a strategy for achieving gadolinium-free contrast agents. Accordingly, polymer coating using poly(isobutylene-alt-maleic anhydride) (PMA) with overcoating of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 72 publications
1
15
0
Order By: Relevance
“…The TGA-DTG curves of NpFeSiIm (gure attached in ESI S7 †) showed a major characteristic decomposition stage at 200 C with a mass loss of 0.88 mg, 15.86%, which could be assigned to the physisorbed water inside the nanoparticle matrix or/and further condensation of the hydroxyl group of silica shell Q 3 (Si(OSi) 3 (OH)) to result in Q 4 (Si(OSi) 4 ). The latter has disappeared aer the fabrication of magnetic nanoparticles with the sugar group since its exposure to reux (heating) condition for two days, which allows the condensation to happen.…”
Section: Nanoparticle Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The TGA-DTG curves of NpFeSiIm (gure attached in ESI S7 †) showed a major characteristic decomposition stage at 200 C with a mass loss of 0.88 mg, 15.86%, which could be assigned to the physisorbed water inside the nanoparticle matrix or/and further condensation of the hydroxyl group of silica shell Q 3 (Si(OSi) 3 (OH)) to result in Q 4 (Si(OSi) 4 ). The latter has disappeared aer the fabrication of magnetic nanoparticles with the sugar group since its exposure to reux (heating) condition for two days, which allows the condensation to happen.…”
Section: Nanoparticle Characterizationmentioning
confidence: 99%
“…In the last decade, the synthesis of nanoparticles was mainly focused on the application of traditional materials science catalysts, 1 , 2 optical coating, 3 , 4 and ceramics. 5 But in the past few years, due to advancements in the synthesis and characterization of nanomaterials, their application has experienced rapid developments.…”
Section: Introductionmentioning
confidence: 99%
“…However, Mag have some limitations in practical application, such as instability (easily oxidized in air), easy agglomeration, problematic distribution and collection [31]. Integrating Mag into other materials to create composite or hybrid materials (e.g., carbon nanotubes with Mag, biopolymers conjugated with Mag) [32][33][34] or coating of Mag with some polymer (e.g., alginate, polyacrylic acid, poly(vinyl alcohol), polyethyleneimine, poly(isobutylenealt-maleic anhydride) polyethylene glycol, starch, methoxypoly(ethylene glycol)) [35][36][37][38][39] are the main strategies used for solving these shortcomings of Mag. Herein, we propose embedding Mag into hydrogel mm-or µm-scale particles (beads) which combine advantages of both (gel particles and Mag)-rapid separation by external magnetic field and/or gravitational settling due to high density, stability against dissolution especially at lower pH of solution, amplified enzyme activity and a number of available methods able to give large amounts of beads under mild and simple preparation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve a proper coating of the magnetic core, a wide range of treatments are available, including chemical vapor deposition, solution plasma processing, hydrothermal methods, spray pyrolysis, and solid-phase synthesis [20][21][22]. It has been demonstrated that IONP encapsulation employing different coatings based on citric acid, lactonic acid, polyvinylpyrrolidone, or polyethylene glycol enhances the chemical, thermal, and colloidal stabilities [23,24]. The treatments mentioned above are well known and efficient.…”
Section: Introductionmentioning
confidence: 99%